1989
DOI: 10.1177/107110078900900608
|View full text |Cite
|
Sign up to set email alerts
|

Pes Planus After Tibial Osteotomy

Abstract: When 100 patients who had had a high tibial osteotomy for monocompartmental arthritis were reviewed, 15 were found to have evidence of neurological impairment. A severe symptomatic pes planus deformity of the ipsilateral limb had developed in 4 patients within months of surgery. Electromyographic results showed evidence of dysfunction in the territory of the posterior tibial nerve in all 4 patients, and, in 3 there was evidence of deep peroneal nerve damage. All had surgery for varus malalignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…The iatrogenic flatfoot may result from over-or undercorrection of many different deformities, such as talipes equino varus, pes cavus, metatarsus adductus, pes planovalgus, or Achilles tendon lengthening (177). A complete review of systems and family history are important in cases of suspected systemic disease.…”
Section: Iatrogenic Post-traumatic or Arthritic Deformity (Pathway 5)mentioning
confidence: 99%
“…The iatrogenic flatfoot may result from over-or undercorrection of many different deformities, such as talipes equino varus, pes cavus, metatarsus adductus, pes planovalgus, or Achilles tendon lengthening (177). A complete review of systems and family history are important in cases of suspected systemic disease.…”
Section: Iatrogenic Post-traumatic or Arthritic Deformity (Pathway 5)mentioning
confidence: 99%
“…Lateral tibial osteotomy includes risk of peroneal nerve palsy 27,29,58 during exposure, proximal fi bular osteotomy, or fi bular head resection. The osteotomy should be performed with the knee in fl exion to reduce tension to the nerve; it also should be kept in mind that fi bular osteotomy to the proximal third carries a higher risk of injury.…”
Section: Complicationsmentioning
confidence: 99%
“…Various studies have reported that MOWHTO causes unintended rotation of the distal tibia and alteration of the posterior tibial slope [11][12][13][14]. MOWHTO can also adversely affect the ankle and knee joints, causing patellofemoral arthritis, pes planus, and gait abnormalities [15][16][17].…”
Section: Introductionmentioning
confidence: 99%